The Society of Thoracic Surgeons National Database. Issue 20 (18th January 2013) - Shahian, David M; Jacobs, Jeffrey P; Edwards, Fred H; Brennan, J Matthew; Dokholyan, Rachel S; Prager, Richard L; Wright, Cameron D; Peterson, Eric D; McDonald, Donna E; Grover, Frederick L
Abstract : Aims: The Society of Thoracic Surgeons (STS) National Database collects detailed clinical information on patients undergoing adult cardiac, paediatric and congenital cardiac, and general thoracic surgical operations. These data are used to support risk-adjusted, nationally benchmarked performance assessment and feedback; voluntary public reporting; quality improvement initiatives; guideline development; appropriateness determination; shared decision making; research using cross-sectional and longitudinal registry linkages; comparative effectiveness studies; government collaborations including postmarket surveillance; regulatory compliance and reimbursement strategies. Interventions: All database participants receive feedback reports which they may voluntarily share with their hospitals or payers, or publicly report. STS analyses are regularly used as the basis for local, regional and national quality improvement efforts. Population: More than 90% of adult cardiac programmes in the USA participate, as do the majority of paediatric cardiac programmes, and general thoracic participation continues to increase. Since the inception of the Database in 1989, more than 5 million patient records have been submitted. Baseline data: Each of the three subspecialty databases includes several hundred variables that characterise patient demographics, diagnosis, medical history, clinical risk factors and urgency of presentation, operative details and postoperative course including adverse outcomes. Data capture: Data are entered by trained data abstractors and by the care team, using detailed data specifications for each element. Data quality: Quality and consistency checks assure accurate and complete data, missing data are rare, and audits are performed annually of selected participant sites. Endpoints: All major outcomes are reported including complications, status at discharge and mortality. Data access: Applications for STS Database participants to use aggregate national data for research are available at http://www.sts.org/quality-research-patient-safety/research/publications-and-research/access-data-sts-national-database .